2013
DOI: 10.1007/s10549-013-2814-5
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus plus exemestane as first-line therapy in HR+, HER2− advanced breast cancer in BOLERO-2

Abstract: The present exploratory analysis examined the efficacy, safety, and quality-of-life effects of everolimus (EVE) + exemestane (EXE) in the subgroup of patients in BOLERO-2 whose last treatment before study entry was in the (neo)adjuvant setting. In BOLERO-2, patients with hormone-receptor-positive (HR+), human epidermal growth factor receptor-2-negative (HER2−) advanced breast cancer recurring/progressing after a nonsteroidal aromatase inhibitor (NSAI) were randomly assigned (2:1) to receive EVE (10 mg/day) + E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 26 publications
0
75
0
2
Order By: Relevance
“…The PFS benefit was especially pronounced in exploratory subgroup analyses of patients who received everolimus plus exemestane (n = 100) as first-line therapy for advanced disease compared with those who had received exemestane alone (n = 37). Everolimus plus exemestane nearly tripled PFS based on local assessment (11.5 months versus 4.1 months for exemestane; HR 0.39; 95% CI 0.25-0.62), and the improvement in PFS with combination therapy was confirmed by central assessment (15.2 months versus 4.2 months; HR 0.32; 95% CI 0.18-0.57) [26]. The BOLERO-2 study also demonstrated that the addition of everolimus to exemestane provided consistent and substantial PFS benefits in several patient subgroups (some of which had limited numbers of patients), including patients with visceral metastases, and regardless of sensitivity to prior endocrine therapy or age [21].…”
Section: Endocrine Therapy In Combination With Molecular-targeted Thementioning
confidence: 84%
See 1 more Smart Citation
“…The PFS benefit was especially pronounced in exploratory subgroup analyses of patients who received everolimus plus exemestane (n = 100) as first-line therapy for advanced disease compared with those who had received exemestane alone (n = 37). Everolimus plus exemestane nearly tripled PFS based on local assessment (11.5 months versus 4.1 months for exemestane; HR 0.39; 95% CI 0.25-0.62), and the improvement in PFS with combination therapy was confirmed by central assessment (15.2 months versus 4.2 months; HR 0.32; 95% CI 0.18-0.57) [26]. The BOLERO-2 study also demonstrated that the addition of everolimus to exemestane provided consistent and substantial PFS benefits in several patient subgroups (some of which had limited numbers of patients), including patients with visceral metastases, and regardless of sensitivity to prior endocrine therapy or age [21].…”
Section: Endocrine Therapy In Combination With Molecular-targeted Thementioning
confidence: 84%
“…In addition, the patient inclusion and exclusion parameters in the 2 studies may have selected for patients with different mechanisms of endocrine resistance, thereby resulting in differences in clinical efficacy. Indeed, the marked activity of everolimus plus exemestane in the first-line subset in BOLERO-2 (all of whom had received prior NSAI in the adjuvant setting) suggests that a key determinant of patient selection might be prior treatment history rather than line of therapy in the advanced setting [26]. Finally, patients with HER2 + status (temsirolimus arm, 23%; control arm, 18%) or unknown HER2 status (temsirolimus arm, 36%; control arm, 35%) were included in the HORIZON study.…”
Section: Endocrine Therapy In Combination With Molecular-targeted Thementioning
confidence: 99%
“…However, the ABC4 panelists (97.4%) recommended consistent monitoring as well as proactive side effect management. They referred to the increased incidence of toxicities and even deaths in older patients in the everolimus-containing arm of the BOLERO-2 study [9,10]. …”
Section: Hr-positive Her2-negative Advanced or Metastatic Breast Cancermentioning
confidence: 99%
“…В исследования включались паци-ентки, которые ранее получали нестероидные ингиби-торы ароматазы. Было установлено, что сочетание эндокринной и mTOR-специфической терапии при-водит к достоверному улучшению результатов лече-ния, в частности увеличению времени до прогресси-рования и общей продолжительности жизни пациенток [15][16][17]…”
Section: истина рождается как ересь а умирает как предрассудок г гunclassified